Exploring the Possible Role of Semiochemicals in Quince (Cydonia oblonga Mill.): Implications for the Biological Behavior of Cydia pomonella - Gomez, María Pía (2026)
The codling moth (Cydia pomonella L.) is a major pest of pome fruits worldwide, guided by semiochemicals to locate hosts and oviposition sites. Quince (Cydonia oblonga Mill.), although less studied, is also affected by this pest. This study aimed to identify behaviorally active compounds for codling moth by characterizing the volatilome of quince cultivars. Volatile profiles were analyzed across four phenological stages (flowering, unripe, growth, and ripe fruit) using solid-phase microextraction and GC–MS. The cultivars evaluated were Champion, INTA 37, INTA 117, and INTA 147. Female oviposition behavior and neonate larval host choice were also assessed. Identified volatiles included esters, sesquiterpenes, monoterpenes, alcohols, aldehydes, and norisoprenoids. Among monoterpenes, limonene, consistently detected across all cultivars and stages, emerged as a key kairomone. Volatile composition varied across phenological stages, with the fruit growth stage exhibiting the highest diversity and abundance of compounds previously reported as behaviorally active. This pattern coincided with peak female oviposition and larval host selection. Females oviposited mainly on leaf surface, whereas during ripening, eggs were deposited on fruit lacking pubescence. Overall, INTA 147 was the most preferred cultivar. These findings highlight quince volatiles, particularly Limonene, as potential candidates for the development of semiochemical-based tools to improve codling moth management.